Caloric restriction delays age-related muscle atrophy by inhibiting 11β−HSD1 to promote the differentiation of muscle stem cells - Lv, Shan; Shen, Qianjin; Li, Hengzhen; Chen, Qun; Xie, Wenqing; Li, Yusheng; Wang, Xiaodong; Ding, Guoxian (Frontiers in Medicine, 2023)
Calorie restriction (CR) is an important direction for the delay of sarcopenia in elderly individuals. However, the specific mechanisms of CR against aging are still unclear. In this study, we used a CR model of elderly mice with muscle-specific 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) knockout mice and 11β-HSD1 overexpression mice to confirm that CR can delay muscle aging by inhibiting 11β-HSD1 which can transform inactive GC(cortisone) into active GC(cortisol). The ability of self-proliferation and differentiation into muscle fibers of these mouse muscle stem cells (MuSCs) was observed in vitro. Additionally, the mitochondrial function and mitochondrial ATP production capacity of MuSCs were measured by mitochondrial oxygen consumption. It was found that the 11β-HSD1 expression level was increased in age-related muscle atrophy. Overexpression of 11β-HSD1 led to muscle atrophy in young mice, and 11β-HSD1 knockout rescued age-related muscle atrophy. Moreover, CR in aged mice reduced the local effective concentration of glucocorticoid (GC) through 11β-HSD1, thereby promoting the mitochondrial function and differentiation ability of MuSCs. Together, our findings highlight promising sarcopenia protection with 40% CR in older ages. Furthermore, we speculated that targeting an 11β-HSD1-dependent metabolic pathway may represent a novel strategy for developing therapeutics against age-related muscle atrophy.